QURAN LITERACY STRENGTHENING TRAINING THROUGH THE TAHSIN METHOD FOR STUDENTS OF THE FIFTY CITY STATE ISLAMIC SCHOOL - Fitri Wahyuningsih; Zoni Leo Nardo; Nana Sepriyanti; Martin Kustati (CV. Naskah Aceh, 2026)
Quranic literacy is an important part of Islamic education, especially at the Madrasah Ibtidaiyah level as a foundation for developing the ability to read, understand, and practice Islamic teachings from an early age. However, at the Lima Puluh Kota State Madrasah Ibtidaiyah, various problems are still found, such as many students who are not yet fluent in reading the Quran, inaccuracy in pronouncing the letters, weak understanding of tajweed, and low interest in reading the Quran. This condition requires real efforts through community service activities in the form of training to strengthen Quranic literacy through the tahsin method. This activity aims to improve students' ability to read the Quran properly and correctly according to the rules of tajweed and strengthen teacher competence in guiding Quranic learning. The service method used is Service Learning with the stages of problem identification, program planning, implementation of tahsin training, direct practice, teacher mentoring, reading evaluation, and pretest and posttest. The implementation of the activity demonstrated an improvement in students' ability to read the Quran, particularly in fluency, accuracy of pronunciation, and application of Tajweed rules. Furthermore, students gained more confidence in reading the Quran, while teachers found it easier to provide ongoing coaching. Thus, this tahsin training made a positive contribution to strengthening Quranic literacy in the madrasah environment.